Subject pro-drop and past-tense auxiliary clitics in South-Western Ukrainian. - Fellerer, Jan (Russian Linguistics, 2022)
South-Western Ukrainian dialects have retained the option of auxiliary clitics in the formation of the past tense. At the same time, they have past-tense forms without auxiliary clitics as in Northern Ukrainian dialects, and in Standard Ukrainian based on South-Eastern dialects. A sample corpus study suggests that South-Western Ukrainian also shows a higher frequency of subject pro-drop than Standard Ukrainian. The South-Western Ukrainian pattern presents the precise mirror image of the same two features in South-Eastern 'Borderland' Polish. Here, the dialect adopted the option of past-tense forms without auxiliary clitics, next to those with them as in Standard Polish. At the same time, it shows a higher frequency of non-pro-drop than Standard Polish. I argue that these matching facts are the result of long- standing language contact that worked simultaneously in two directions: the increase in the use of an existing dialectal Ukrainian pattern under Polish influence, as well as the increase in the use of an existing dialectal Polish pattern under Ukrainian influence. As a result, both dialects show the same variation between past-tense forms with auxiliary clitics and without them, and they have mutually converging tendencies in subject pro-drop – the Ukrainian dialect adapting towards Polish pro-drop, and the Polish dialect towards Ukrainian non-pro- drop. The bi-directionality of influence in the SWU dialectal area, thus, goes beyond other, unidirectional language-contact scenarios.